Kemampuan Menemukan Kalimat Utama dalam Paragraf Deduktif dengan Menggunakan Model Pembelajaran Inquiry pada Siswa Kelas VII SMP St. Paulus Benteng Jawa - Falentinus Bata; Yuliana T. Wati (Journal on Education, 2023)
This study aims to determine the ability to find main sentences in deductive paragraphs using the Inquiry learning model in class VII students of SMP St. Paul Fort Java. This study uses a quantitative approach. The data collection technique used in this study is the test technique. After the data is collected, the data is analyzed using the written test method then the data is presented formally, meaning that the data is described using numbers. The theory used in this study is the theory of learning evaluation and syntax theory. The results of the study showed that students at St. Middle School. Paulus Benteng Jawa is classified as capable because the average score obtained by all sample students is 87.6% and students who are able are 63 people with a percentage of 84% and students who are unable are 12 people with a percentage of 16%.